ANALISIS TERHADAP PENERAPAN THEORY OF CONSUMER ACCEPTANCE TECHNOLOGY PADA E-SPT - Prita Saraswati; Endang Kiswara (Diponegoro Journal of Accounting, 2013)
This study aims to predict the factors that influence taxpayer behavior towards the use of E-SPT interests in Indonesia. This research is a replication of the study Kulviwat, et al. (2007) that integrates Technology Acceptance Model (TAM) by Pleasure, Arousal, and Dominance (PAD) into a model of Consumer Acceptance Technology (CAT). The research was conducted on corporate taxpayers in Jakarta, Indonesia. The object of this research is the application of taxes in particular E-SPT was developed by the Indonesian Directorate General of Taxation. The sample used in this study were 57 companies that have used the tax application in particular E-SPT. Data analysis method used is Smart PLS 2.0.This study uses the variable perceived of relative advantage, perceived usefulness, perceived ease of use, pleasure, arousal, dominance, attitudes, and intentions in using E-SPT. The results of this study indicate that the taxpayer attitudes are the main factors affecting the taxpayers interest in using e-SPT. Consumer Acceptance Technology (CAT) can be integrated as a research model for explaining the corporate taxpayers to use E-SPT.The results of this study showed that the perceived of relative advantage, pleasure, arousal, and dominance have significant and positive impact on the attitude required to use E-SPT. Perceived usefulness and perceived ease of use have no significant effect on the attitude of taxpayers to use E-SPT. So, to increase the use of E-SPT returned by the taxpayer perceived of relative advantage, pleasure, arousal, and dominance of E-SPT need to be improved.